Performance of multiple space time coded MIMO-OFDM by using equalizer method / Noorhafishah Hanafi - Hanafi, Noorhafishah (2007)
This project highlights the simulation by using Space Time Block Code to identify the effect of two type of noise which is Additive White Gaussian Noise and Multipath Rician Fading to a communication system. The main objective is to compare the performance of Bit Error Rate (BER) at the communication channel with Additive White Gaussian Noise or Multipath Rician Fading. Space Time Block Code scheme combines the channel code design with modulation and diversity at the transmitter to improve the data rates and reliability of communication. This technology is primarily concerned with three dimensional (3-D) signal design for multi-transmit antenna wireless systems. Beside that the design of STBC is to achieve full spatial diversity over fading channels. Matlab Version 2006a is used to simulate the system. The model consists of transmitter, transmission channel and receiver. The adaptive equalizer method is used at the receiver to equalize the output signal. The system also provides error detection and correction using Forward Error Correction (FEC).